Clinical and immunological factors associated with the progression of Lupus Nephritis in a population from the Colombian Caribbean (2024)
Lupus nephritis represents a significant immune-mediated glomerulonephritis, constituting the most important organ involvement induced by systemic lupus erythematosus (SLE), with variable epidemiology and clinical presentation among populations. Objective: to identify clinical and immunological factors associated with the progression of lupus nephritis in a population from the Colombian Caribbean. Methods: we evaluated 401 patients diagnosed with SLE and lupus nephritis, treated at a reference center in the Colombian Caribbean, gathering data recorded in medical records. Results: A proportion of 87% were female, with a median age of 42 years. Most patients presented with proliferative classes (90%), with class IV being the most common (70%). A proportion of 52% of patients did not respond to treatment, which is described as the lack of complete or partial response, while 28% had a complete response. A significant decrease in hemoglobin, glomerular filtration rate, and proteinuria was identified by the third follow-up (p < 0.001), along with an increase in creatinine, urea, and hematuria (p < 0.001). Patients with initial proteinuria > 2 g/day were found to be 27 times more likely to be non-responders (p < 0.001). Mortality was associated with the presence of serum creatinine >1.5 mg/dL (p = 0.01) (OR: 1.61 CI 95% 0.75–3.75) and thrombocytopenia (p = 0.01) (OR: 0.36; CI 95% 0.12–0.81). Conclusions: identifying factors of progression, non-response, and mortality provides an opportunity for more targeted and personalized intervention, thereby improving care and outcomes for patients with lupus nephritis.